Subclinical Carditis in Acute Rheumatic Fever: A Single Center Experience - Alam, Md. Saidul; Hye, Mohammad Abdul; Ahmed, Shuperna; Islam, Mohammad Aminul; Lubna, Mustanshirah; Bhattacharjee, Biplob; Rahman, Md. Arifur; Jobayer, Mohammad (Cardiology and Cardiovascular Medicine, 2023)
Background: Acute rheumatic fever (ARF) is an important public health problem in developing countries. Subclinical carditis (SCC) that is detected only by echocardiogram without audible heart murmurs is relatively common in ARF. The aim of this study was to determine the pattern of SCC in patients of ARF in a specialized center in Bangladesh. Methods: This cross-sectional study was conducted from April 2019 to May 2021 at the National Center for Control of Rheumatic Fever and Heart Diseases. Hundred consecutive diagnosed patients of acute rheumatic fever with SCC were included in the study. Diagnosis of ARF was done according to the revised Jones criteria in 2015. A total of 362 clinically suspected patients of ARF were screened and among them, 100 patients were detected of having SCC by Doppler echocardiography. Results: Mean age of patients with ARF and SCC was 11.8 ±3.6 years and 10.8 ±3.3 years respectively and female was predominant (52.6% in ARF and 57.7% in SCC). Majority of patients (94%) with SCC had a mitral valve involvement and isolated mitral regurgitation was the most common (84%) valvular lesion. Detected valvular lesions mostly were not severe; all the aortic regurgitation and almost all mitral regurgitation (98.8%) were mild and trivial in nature of severity. Conclusion: Common presence of SCC among ARF patients in our study agreed with the recommendations of revised Jones Criteria. Therefore, it is suggested that echocardiography should be done in every suspected patient with ARF for early detection of subclinical carditis and to reduce morbidity.